2014
DOI: 10.3892/mmr.2014.2435
|View full text |Cite
|
Sign up to set email alerts
|

Rat hepatic stellate cells alter the gene expression profile and promote the growth, migration and invasion of hepatocellular carcinoma cells

Abstract: The aim of the present study was to examine the effects of activated hepatic stellate cells (HSCs) and their paracrine secretions, on hepatocellular cancer cell growth and gene expression in vitro and in vivo. Differentially expressed genes in McA-RH7777 hepatocellular carcinoma (HCC) cells following non-contact co-culture with activated stellate cells, were identified by a cDNA microarray. The effect of the co-injection of HCC cells and activated HSCs on tumor size in rats was also investigated. Non-contact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Multiple studies have shown poor survival as well as increased metastasis and recurrence following resection in HCC patients with positive HSC gene signatures or high expression of α-SMA (50, 53, 80, 81). Similar findings were made in animal models, where coinjection of activated HSC and HCC cells into mice enhanced subcutaneous or orthotopic tumor growth (53, 8085). However, these studies lacked the proper hepatic environment in which HCCs develop and progress and may have led to unphysiological interactions between HSC and HCC cells that normally do not occur in hepatocarcinogenesis.…”
Section: Hepatocellular Carcinomasupporting
confidence: 77%
“…Multiple studies have shown poor survival as well as increased metastasis and recurrence following resection in HCC patients with positive HSC gene signatures or high expression of α-SMA (50, 53, 80, 81). Similar findings were made in animal models, where coinjection of activated HSC and HCC cells into mice enhanced subcutaneous or orthotopic tumor growth (53, 8085). However, these studies lacked the proper hepatic environment in which HCCs develop and progress and may have led to unphysiological interactions between HSC and HCC cells that normally do not occur in hepatocarcinogenesis.…”
Section: Hepatocellular Carcinomasupporting
confidence: 77%
“…A bi-directional cross-talk between hepatocytes and HSCs has been previously described [1,2,16]. A bi-directional cross-talk between hepatocytes and HSCs has been previously described [1,2,16].…”
Section: Hsc and Hepatocyte Interactions Induce Crp Expression But Nomentioning
confidence: 99%
“…Both direct cell-cell interactions and soluble factors/cytokines from these interactions contribute to a proinflammatory and profibrotic microenvironment [1,2]. HSCs are in close contact and interact with hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Increased proliferation, migration and invasion capacity of HCC cells when cultured in activated LX-2 conditioned medium [58] (Continued) Co-culture Hep3B Accelerated tumor cell/HSC spheroid formation in 3D culture system [35] McA-RH7777 Increased secretion of HGF, IL-6, MMP2, and MMP9 from HCC cells when co-cultured with rat HSCs [36] HepaRG, HuGB, Huh7, HepG2…”
Section: Hscs May Decrease Immune Surveillancementioning
confidence: 99%
“…McA-RH7777 Increased tumor weight and volume in HCC cells co-injected with culture-activated rat HSCs [36] MIMR Twofold increase in tumor formation resulting from co-transplantation with M1-4HSCs [38] Hepa1-6 Increased tumor proliferation and volume due to increased Treg accumulation [61] H22 Increased tumor volume resulting from decreased lymphocyte infiltration, increased apoptosis of mononuclear cells, and increased Treg infiltration in tumor [60] MHCC97H Accelerated tumor growth when co-injected with LX-2 cells [58] Orthotopic co-transplantation H22 Threefold increase in tumor burden resulting from increased angiogenesis, lymphangiogenesis, and increased infiltration of Tregs and myeloid-derived suppressor cells [52] MHCC97L Decreased metastatic ability of HCC cells when co-injected with epimorphin-null LX-2 cells [58] (Continued)…”
Section: Hscs May Decrease Immune Surveillancementioning
confidence: 99%